Fpga Implementation Of Digital Modulation Schemes Using Verilog Hdl - et. al., Hemanth Kumar S N, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper describes the design and development of an FPGA-based digital Modulation Scheme for high-resolution Communication Application. We are focusing on implementation of Verilog based code simulation for fundamental and widely used digital modulation techniques such as Binary Amplitude-shift keying (BASK), Binary Frequency-shift keying (BFSK), Binary Phase-shift keying (BPSK) and Quadrature Phase Shift Keying(QPSK). In this work the idea of sinusoidal signals that have been generated is plain sailing in nature and based on fundamentals of signal sampling and quantization. Such concept of sinusoidal signals generation is not unfamiliar but somehow simplified using sampling and quantization in time and amplitude domain, respectively. The whole simulation is done on Modelsim and Xilinx-ISE using VERILOG Hardware descriptive language. The work has been accomplished on Thirty two bit serial data transmission with self-adjustable carrier frequency and bit duration length.